Gender Ideals Violation in Domestic and Economic Life as Found in Margaret Mitchell’s Gone With The Wind - setyowati, Lestari - (Humaniora, 2017)
This study aimed at describing the violation of gender ideals of the main female character in Margaret Mitchell’s Gone with the Wind in relation to domestic and economic life and describing the possible reasons of why she violated them. The design used was content analysis in qualitative paradigm. Codifications and indicators were established to help to analyze the data. The theories used to analyze the data were the expansionist theory in gender, the Freudian Psychological theory, and the self-actualization theory. The finding shows that Scarlett O’Hara has violated the domestic ideals as a belle, wife, mother, and widow. She also violates the Victorian rules dealing with women and economic life. Scarlett’s violation of the rules in her society is caused by the internal factor and the external factor, the Civil War. It is the emergency, the occasion, and the condition at that time that makes her violate them. Her controversial acts in her society can be considered as a constructive change as it gears to women improvement and equality. The violation of gender ideals of her time does not always mean a negative deviation. It can also bring improvement for a better life.